The effect of aggregate and mineral admixtures on engineering properties of high strength self compacting concrete / Omar Riyadh Khaleel - Omar Riyadh , Khaleel (2013)
This study deals with producing high strength self compacting concrete (HSSCC) using locally available materials. The work was conducted in three parts i.e. paste, mortar and concrete to facilitate the mix design process. The effect of using powder materials and superplasticizer on properties of paste, mortar and concrete as well as the effect of coarse aggregate properties namely volume, maximum size, grading, and shape on the properties of concrete were investigated. For the study on mortar, fly ash (FA) and metakaolin (MK) as pozzolan while limestone powder and kaolin as filler material were used at replacement levels of 5%, 10%, 15%, and 20% by weight of cement and sand, respectively. Self compactibility of mortars was obtained by adding suitable materials such as mineral admixtures and superplasticizer which provided a sufficient balance between flowability and viscosity of the mix. The optimum replacement level of FA and MK for cement was 10% from the viewpoint of workability and strength, while the optimum replacement level of limestone for sand was 20%. Flowability of mortar increased with the use of fly ash and decreased with the use of metakaolin and kaolin. Moreover, strength of mortar increased when the optimum replacement level of pozzolan and limestone powder was used. Different fresh concrete tests were adopted. Slump flow spread and V-funnel tests were used to determine the filling ability, L-box and J-ring tests were used to determine passing ability and segregation index test to determine segregation resistance. The results obtained for fresh concrete properties showed that flowability of concrete increased with increase flowability of mortar. The mixes which contained coarse aggregate with higher volume, larger size, non continuous grading and high flakiness ratio affected negatively the fresh properties of HSSCC. The results for the hardened concrete showed better strengths and stiffness as well as good durability for limestone powder, metakaolin, fly ash mixes in the respective order. Higher shrinkage was obtained for the limestone, fly ash mixes in the respective order, while control and metakaolin mixes showed lower shrinkage. The 33% coarse aggregate volume in the mixes was the optimum volume from the viewpoint of strengths and stiffness compared to other volumes. The increase in aggregate volume reduced the shrinkage. Moreover, the strengths and stiffness increased for mixes containing coarse aggregate with smaller particle fractions, continuous grading and low flakiness ratio. Drying shrinkage of the mixes decreased when the larger particles were used while the use of non graded aggregate and flaky particles led to increase in shrinkage. This study concludes that the use of powders gave good workability and strength and thus would reduce the use chemical admixtures and cement and consequently reduce the cost. The flowability of mortar has a great role in affecting the flowability of concrete. Good correlations were found between the results of the fresh and hardened tests for HSSCC, and an equation is proposed to estimate the coarse aggregate volume for HSSCC using the flowability of mortar. It is feasible to produce HSSCC with different powders and different aggregate properties.